STRATEGI MARKETING PEGAWAI BANK SYARIAH DALAM MEREKRUT NASABAH DI BANK SYARIAH INDONESIA KCP PLERED 2 - Muhammad Maulidin; Salis Apriliani; Achmad Nurjannah (IAIC (Institut Agama Islam Cirebon), 2022)
Currently, Islamic banking is growing rapidly, along whith these developments, employee marketing strategies mush also increase. To increase the number of customers, Islamic banks need a strategy in each of their sales products that aim to develop business at Indonesian Islamic bank KCP Plered 2. The purpose of this study was to find out how the marketing strategy of Islamic bank employees in Islamic banks Indonesia KCP Plered 2. This study uses a qualitative method with a descriptive approach, where the data obtained is by interviewing each marketing employee and also the director of Islamic banks. The results of this study indicate that the marketing strategy used in recruiting customers is to use a marketing mix strategy. Marketing mix is a form of marketing strategy that is carried out by combining several elements in integrated manner including those commonly known as the 5 (P) namely Product, Price, Promotion, Place, People. A very important role in recruiting customers in BSI Plered 2 is by using a promotion strategy itself used in recruiting customers at BSI KCP Plered 2 is pcking up the market, advertising, sales promotion, socialization, and personal selling.